Family C G-Protein-Coupled Receptors in Alzheimer’s Disease and Therapeutic Implications - Dal Prà, Ilaria; Armato, Ubaldo; Chiarini, Anna (Frontiers in Pharmacology, 2019)
Alzheimer’s disease (AD), particularly its sporadic or late-onset form (SAD/LOAD), is the most prevalent (96–98% of cases) neurodegenerative dementia in aged people. AD’s neuropathology hallmarks are intrabrain accumulation of amyloid-β peptides (Aβs) and of hyperphosphorylated Tau (p-Tau) proteins, diffuse neuroinflammation, and progressive death of neurons and oligodendrocytes. Mounting evidences suggest that family C G-protein-coupled receptors (GPCRs), which include γ-aminobutyric acid B receptors (GABABRs), metabotropic glutamate receptors (mGluR1-8), and the calcium-sensing receptor (CaSR), are involved in many neurotransmitter systems that dysfunction in AD. This review updates the available knowledge about the roles of GPCRs, particularly but not exclusively those expressed by brain astrocytes, in SAD/LOAD onset and progression, taking stock of their respective mechanisms of action and of their potential as anti-AD therapeutic targets. In particular, GABABRs prevent Aβs synthesis and neuronal hyperexcitability and group I mGluRs play important pathogenetic roles in transgenic AD-model animals. Moreover, the specific binding of Aβs to the CaSRs of human cortical astrocytes and neurons cultured in vitro engenders a pathological signaling that crucially promotes the surplus synthesis and release of Aβs and hyperphosphorylated Tau proteins, and also of nitric oxide, vascular endothelial growth factor-A, and proinflammatory agents. Concurrently, Aβs•CaSR signaling hinders the release of soluble (s)APP-α peptide, a neurotrophic agent and GABABR1a agonist. Altogether these effects progressively kill human cortical neurons in vitro and likely also in vivo. Several CaSR’s negative allosteric modulators suppress all the noxious effects elicited by Aβs•CaSR signaling in human cortical astrocytes and neurons thus safeguarding neurons’ viability in vitro and raising hopes about their potential therapeutic benefits in AD patients. Further basic and clinical investigations on these hot topics are needed taking always heed that activation of the several brain family C GPCRs may elicit divergent upshots according to the models studied.